Karakteristik Warna Mikroplastik di Perairan Sungai Jawi Kecamatan Sungai Kakap Kabupaten Kubu Raya - Nh, Rozza Nabilla; Munir, Achmad Mulyadi Sirojul; Kurniadi, Bambang (Akuatik Tropis (Akuatrop): Journal of Tropical Aquatic Resource Management (ISSN:3063-7414), 2026)
Microplastic pollution in tropical river waters such as the Jawi River, Sungai Kakap District, Kubu Raya Regency, West Kalimantan is increasingly worrying due to anthropogenic activities such as domestic waste. This study aims to identify the color and abundance of microplastics. Water samples (20 L/station) were taken from 6 purposivestations using a 40 μm mesh plankton net, identified through saturated NaCl density separation and a binocular microscope. The total abundance reached 998 particles/L, dominated by transparent colors (957 particles/L), yellow (13 particles/L), blue (13 particles/L), black (8 particles/L), pink (3 particles/L), purple (2 particles/L), red (1 particle/L) and green (1 particle/L). Environmental parameters: pH 6.45-7 (neutral), DO 3-7 mg/L (low upstream), salinity 0-5 ppt (upstream), brightness 16-72 cm. One-Way ANOVA test showed no significant difference between stations (Sig. 0.917 > 0.05). Multiple regression of physico-chemical parameters with color abundance was not significant (all Sig. >0.05, R = 0.269). Transparent color was dominant at the estuary station (high salinity), black accumulation in the upstream (low DO), indicating the source of new plastic packaging and degraded pollutants from domestic/fishery activities. This study is the basis for plastic waste management based on color characteristics in the Jawi River.